Validity and diagnostic performance of fluorescence optical imaging measuring synovitis in hand osteoarthritis: baseline results from the Nor-Hand cohort - Øystein Maugesten; Alexander Mathiessen; Hilde Berner Hammer; Sigrid Valen Hestetun; Tore Kristian Kvien; Till Uhlig; Sarah Ohrndorf; Ida Kristin Haugen (Arthritis Research & Therapy, 2020)
Abstract Objective Fluorescence optical imaging (FOI) demonstrates enhanced microcirculation in finger joints as a sign of inflammation. We wanted to assess the validity and diagnostic performance of FOI measuring synovitis in persons with hand OA, comparing it with magnetic resonance imaging (MRI)- and ultrasound-detected synovitis. Methods Two hundred and twenty-one participants with hand OA underwent FOI and ultrasound (gray-scale synovitis and power Doppler activity) of the bilateral hands and contrast-enhanced MRI examination of the dominant hand. Fifteen joints in each hand were scored on semi-quantitative scales (grade 0–3) for all modalities. Four FOI images were evaluated: one composite image (Prima Vista Mode (PVM)) and three images representing phases of fluorescent dye distribution. Spearman’s correlation coefficients were calculated between sum scores of FOI, MRI, and ultrasound. Sensitivity, specificity, and area under the curve (AUC) were calculated for FOI using MRI or ultrasound as reference. Results FOI did not demonstrate enhancement in the thumb base, and the joint was excluded from further analyses. FOI sum scores showed poor to fair correlations with MRI (rho 0.01–0.24) and GS synovitis sum scores (rho 0.12–0.25). None of the FOI images demonstrated both good sensitivity and specificity, and the AUC ranged from 0.50–0.61 and 0.51–0.63 with MRI and GS synovitis as reference, respectively. FOI demonstrated similar diagnostic performance with PD activity and GS synovitis as reference. Conclusion FOI enhancement correlated poorly with synovitis assessed by more established imaging modalities, questioning the value of FOI for the evaluation of synovitis in hand OA.